Malignant pleural effusion management: keeping the flood gates shut. Issue 6 (June 2020) - Walker, Steven; Mercer, Rachel; Maskell, Nick; Rahman, Najib M
Summary: With no cure for malignant pleural effusion, efforts are focused on symptomatic management. Historically, this symptomatic management was achieved with the instillation of a sclerosant agent into the pleural space to achieve pleurodesis. The development of the tunnelled indwelling pleural catheter and ambulatory pleural drainage changed the management of malignant pleural effusion, not solely by offering an alternative management pathway, but by challenging how health-care providers view success in a palliative condition. Furthermore, with additional treatment options available, increased imperative exists to better characterise patients to enable a personalised approach to their care. We have done a review of the scientific literature and clinical trial registries to provide an overview of the current and ground-breaking research published in the past 10 years.